2018
DOI: 10.3389/fneur.2018.00689
|View full text |Cite
|
Sign up to set email alerts
|

Stenting the Superior Petrosal Sinus in a Patient With Symptomatic Superior Semicircular Canal Dehiscence

Abstract: Patients presenting superior semicircular canal dehiscence (SSCD) can experience symptoms such as conductive hearing loss, pulsatile tinnitus, autophony, and pressure-induced vertigo. Decreased cervical vestibular-evoked myogenic potentials (cVEMPs) thresholds and high-resolution computed tomography (HRCT) of the petrous bone are essential for diagnosis of SSCD syndrome. We report the case of a 43-year-old man suffering from constant right pulsatile tinnitus, intermittent autophony, and unsteadiness induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The implementation of this classification could also bring a potential addition to develop other treatment methods in the future. As an example, in case of a type II (vestibular-vascular) OCD showing a mass effect on the membranous labyrinth highlighted by 3D MRI, performing an endovascular procedure rather than performing a plugging-type surgery was simplest and with no expected vestibular or auditory impairments (24)(25)(26). So far, it appears to be difficult to propose a correlation between symptoms or signs and each type or subtype of OCD, since there is a wide spectrum of clinical presentations that cannot be necessarily systematized (13,14,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of this classification could also bring a potential addition to develop other treatment methods in the future. As an example, in case of a type II (vestibular-vascular) OCD showing a mass effect on the membranous labyrinth highlighted by 3D MRI, performing an endovascular procedure rather than performing a plugging-type surgery was simplest and with no expected vestibular or auditory impairments (24)(25)(26). So far, it appears to be difficult to propose a correlation between symptoms or signs and each type or subtype of OCD, since there is a wide spectrum of clinical presentations that cannot be necessarily systematized (13,14,20).…”
Section: Discussionmentioning
confidence: 99%
“…As for the dehiscence's involving the IJV bulb and labyrinthic membranous structures (VA and the PSC), Thenint et al had already proposed in a limited series stenting of the IJV to limit the transmission of vascular vibrations to the labyrinth with good results ( 24 ). We proposed a similar approach in one of our patients with SSCD by SPS; a significant improvement was observed after the endovascular procedure, which consisted in stenting the SPS ( 25 ). Recently, a similar, although slightly modified, approach was used by another otologic group, since the SPS was just occluded ( 26 ) with a very good result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Another report showed that stenting of the SPS significantly decreased the symptoms of superior semicircular canal dehiscence by the SPS. 36 The CSA of the SPS is relatively easy to examine compared to the degree of EH. If we can efficiently predict the future development of EH in patients from small SPS CSA values, we may be able to prevent the onset of MD by early lifestyle changes.…”
Section: Superior Petrosal Sinus and Ehmentioning
confidence: 99%
“…Because of the fragility, microscopic dimensions and complexity of the inner ear structures, relatively few steps have been taken to date in the specific field of treatments dedicated to the inner ear diseases. In this context, our aim is to develop an artificial vestibular system [4][5][6] that thoroughly represents the physiology of the inner ear in order to sustain or confirm new pathophysiological mechanism theories and to propose new treatment procedures [7][8][9].…”
Section: Introductionmentioning
confidence: 99%